Soil Microorganisms and Seaweed Application With Supplementary Irrigation Improved Physiological Traits and Yield of Two Dryland Wheat Cultivars - Najafi Vafa, Zahra; Sohrabi, Yousef; Mirzaghaderi, Ghader; Heidari, Gholamreza (Frontiers in Plant Science, 2022)
To evaluate the effect of useful soil microorganisms and organic compounds on physiological characteristics and yield of two wheat cultivars under supplementary irrigation conditions, a study was conducted in the Agriculture Research farm of Kurdistan University during the two cropping seasons of 2017-2018 and 2018-2019. A split-split plot based study on a randomized complete block design with four replicates was used as an experimental design. The main factor was irrigation at three levels, including control without irrigation, supplementary irrigation in the booting stage and supplementary irrigation in the booting and flowering stages. Two wheat cultivars including Sardari and Sirvan as sub-factors and application of bio-fertilizers in eight levels, including the use of bio-fertilizers containing: Mycorrhiza, Seaweed extract, Nitrozist and Phosphozist, Mycorrhiza + Nitrozist and Phosphozist, Seaweed extract + Nitrozist and Phosphozist, Mycorrhiza + Seaweed extract, Mycorrhiza + Nitrozist and Phosphozist + Seaweed extract and non-application of bio-fertilizers were considered as sub-factors. The results of both seasons of the experiment showed that the application of bio-fertilizers compared to the control treatment at all irrigation levels increased root volume, leaf relative water content (RWC), membrane stability index (MSI) and photosynthetic pigment content. The highest amount of H2O2, proline and soluble carbohydrates was obtained in wheat under dry land conditions and supplementary irrigation, especially twice irrigation, significantly reduced the values of these traits. Supplementary irrigation also increased grain yield so that in the conditions of twice irrigation compared to the non-irrigation treatment (dry land), in the first and second season of grain yield increased 79.51 and 78.69%, respectively. Application of bio-fertilizers (Mycorrhiza + Nitrozist and Phosphozist + Seaweed extract) in comparison with the non-application of these fertilizers, due to increased root volume, RWC, MSI and content of photosynthetic pigments, increased the grain yield in the first and second seasons of the experiment by 8.04 and 6.96% respectively. As a result, suitable microorganisms and seaweed can improve wheat resistance mechanisms to water deficit, which along with using supplementary irrigation that saves water consumption improves plant growth and yield in areas faced with water shortage.